2022
DOI: 10.1186/s13018-022-03301-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of conservative treatment for spastic cerebral palsy children with equinus gait: a systematic review and meta-analysis

Abstract: Background Comparisons between various conservative managements of spastic equinus deformity in cerebral palsy demonstrated limited evidences, to evaluate the efficacy of conservative treatment among cerebral palsy children with spastic equinus foot regarding gait and ankle motion. Methods Studies were identified from PubMed and Scopus up to February 2022. Inclusion criteria were randomized controlled trial (RCT), conducted in spastic cerebral pals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
(143 reference statements)
0
3
0
1
Order By: Relevance
“…Atualmente, não há consenso sobre o melhor tipo de AFO para pacientes nessa condição, podendo ser órteses sólidas ou articuladas. Contudo, existem orientações acerca da acomodação do comprimento completo do gastrocnêmio nas AFOs e contraindicação em casos de comprimento e rigidez do gastrocnêmio, tanto em alongamento passivo quanto à hipertonicidade (Klaewkasikum et al, 2022).…”
Section: Resultsunclassified
“…Atualmente, não há consenso sobre o melhor tipo de AFO para pacientes nessa condição, podendo ser órteses sólidas ou articuladas. Contudo, existem orientações acerca da acomodação do comprimento completo do gastrocnêmio nas AFOs e contraindicação em casos de comprimento e rigidez do gastrocnêmio, tanto em alongamento passivo quanto à hipertonicidade (Klaewkasikum et al, 2022).…”
Section: Resultsunclassified
“…However, Horsch ( 58 ) proposed a clinical cutoff of a ≤5° dorsiflexion as the recommended value for defining functionally relevant equinus foot in patients with CP. Casting, orthoses, and physical therapies, such as shock waves, botulinum toxin, and surgery, are common treatments for the equinus foot in patients with CP ( 59 61 ). Horsch evaluated gait outcomes and strength following different surgical procedures of the equinus foot in two groups of patients with CP and found that the Strayer procedure and Achilles tendon lengthening showed higher postoperative dorsiflexion.…”
Section: Discussionmentioning
confidence: 99%
“…The most common cause of ankle OA is previous trauma, unlike knee OA, which occurs as a result of the primary OA. Thus, ankle OA patients are usually younger than knee OA patients (Boffa et al, 2021; Ding et al, 2023; Laohajaroensombat et al, 2023). Treatments that are considered for OA of the knee, depending on the severity of the deterioration, include pharmacological treatment, physiotherapy, bracing, prolotherapy, and surgical operation (Hsiao et al, 2021).…”
Section: Introductionmentioning
confidence: 99%